Simulation of rolling moment induced by various aircraft trailing vortices vortex models: review and analysis - Djojodihardjo, Harijono (WSEAS Press, 2015)
It is well known that the trailing vortices which reflect the lift as well as drag characteristics of the aircraft could be optimized for better aircraft performance characteristics and reduction of environmental impact as well as hazardous interference to other flight vehicles and/or objects. Attention is given to identify the stability of various configurations of vortices, vortex decay and means of reducing vortex hazard. Passive wake vortices alleviation systems utilize the natural evolution of the instability modes with the highest growth rates while active systems rely on accelerating selected modes of instability by imposing the vortices individually or as a system. The passive system is essentially a vortex wake, hence an aerodynamic surface design, while an active system is an actuator design effort, respectively. Within such frame of thought, various vortex Aircraft Trailing Vortices Vortex Models are reviewed and analyzed in view of their potentials Wake Hazard Alleviation, by simulating the rolling moment induced. The simulation of various vortex model chosen are judged by their expected characteristics that may reproduce actual state of affairs.